Efeito agudo e crônico do exercício resistido de alta intensidade sobre o torque, atividade eletromiográfica do vasto lateral e freqüência cardíaca de homens idosos - Quitério, Robison José (Universidade Federal de São Carlos, 2007)
The objective of this study was to investigate the acute and chronic effects of high intensity resistance physical exercise on the magnitude of maximal average torque response normalized by body mass (MAT), RMS amplitude of eletromyographic signals (EMGs) of the vastus lateralis and heart rate variation (∆HR). Subjects were nine non-smoking men (ages 61.7+1.7 years, weight 72.5+6.5 Kg., height 1.69+0.06 meters) with an active lifestyle, who did not use medications or any type of drug, and were evaluated as healthy by laboratory tests and clinical examination. The experimental protocol was carried out with the volunteer in seated position with hip flexed at 85º in a computerized isokinetic dynamometer (Biodex Multi Joint System III) and consisted of 6 tests of maximal voluntary contraction (MVC): 10 sec. of isometric knee flexion at 30º (IEx) and isometric extension at 60º (IF); 5 MVC concentric of the knee at 60º/s (C60) and 8 at 120º/s (C120); 5 MVC eccentric of the knee at 60º/sec. (E60) and 8 at 120º/sec. (E120). The values for MAT were normalized for body mass (N.m/Kg). EMGs of the vastus lateralis were registered; RMS amplitude values of eletromyographic signals were calculated and then normalized for RMS of MVC isometric knee extension at 60o. HR was recorded beat to beat in bpm for 60 seconds at rest, during tests and for 120s during recuperation, by a one-channel heart monitor (TC 500 ECAFIX), interfaced to a microcomputer (PC-AT 486 DX-4) by an analogdigital converter (Lab.PC + National Instruments, Co.). The volunteers were monitored at modified MC5 derivation. For the variables studied (MAT, EMGs and HR), the mean of 3 repetitions of each test was calculated for later statistical analysis. At an intensity of 70-80% of MVC, the volunteers performed 2-4 series of 8-12 repetitions of eccentric resistance exercises in twice weekly sessions at angular velocity of 60º/s for three months. The intensity was corrected from fortnightly evaluations of the torque peak. At the end of the training period the same ones were revalued. The MAT eccentric was similar to the isometric and both were superior to the concentric in both flexion and extension. The MAT in C60 was greater than C120 for flexion and extension. The RMS of the concentric tests were superior to the eccentric (P<0,05). The ∆HR (heart rate variation) for the isometric tests was smaller than those for the dynamic (P<0,05). After training was verified: significant increase of MAT eccentric at 60o/s and 120o/s for flexion and extensior; increase in RMS at IEx, C60Ex, E60Ex e E120Ex; ∆HR was greater in the concentric tests at 120o/s and eccentric at 60o/s. The data suggest that: greater MAT and lower EMG values during eccentric exercise, when compared to values obtained during concentric contractions, may be attributed to an additional contribution of passive elastic components to the greater force during eccentric contractions; the ∆HR depends on the mechanics of the exercise (static or dynamic) and is independent of torque level, magnitude of muscular activation and angular velocity during short duration exercise; after resistance training only MAT adaptations were observed to be mode specific as no such adaptations occurred in relation to EMGs and ∆HR.
Keywords: Envelhecimento; Dinanômetro isocinético; Exercício físico concêntrico; Exercício físico excêntrico; Exercício físico isométrico; Eletromiografia; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL